Humanization of Arabic Language Learning in Islamic Higher Education: Integrating Humanitarian and Ethical Values - Ika Wahyu Susiani; Ririn Nuraini; Dinda Nadiasari (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2025)
The global humanitarian crisis shows the limitations of education that is oriented towards knowledge transfer alone. In Islamic higher education, this is reflected in the learning of Arabic which still emphasizes linguistic aspects, thus ignoring the ethical and humanitarian dimensions. Therefore, the humanization of Arabic language learning is an urgency to affirm its role as a medium for internalizing human and Islamic values. In this context, Arabic language education in higher education institutions has long been predominantly linguistics-oriented, often overlooking its transformative potential in fostering humanistic and ethical values. This study aims to describe the integration of humanitarian and ethical values into Arabic language pedagogy in higher education, using a case study conducted in the Arabic Language Education Program at the Institut Agama Islam Riyadlotul Mujahidin Ngabar, Ponorogo. Employing a descriptive qualitative approach, data were collected through classroom observations, in-depth interviews with lecturers and students, and documentation analysis. The research findings show that the integration of humanistic and ethical values in learning is realized through the application of pedagogical strategies in the form of empathetic dialogue that encourages students' reflective participation, as well as experience-based learning that packages material with students' social and humanitarian realities. This integration contributes to enhancing the quality of the learning process, improving students’ pragmatic competence, and producing graduates who are not only linguistically proficient but also embody Islamic ethical character, moderation, and the capacity to model ethical communication.